2017
DOI: 10.1007/s11701-017-0737-6
|View full text |Cite
|
Sign up to set email alerts
|

Robotic radical prostatectomy with concomitant repair of inguinal hernia: is it safe?

Abstract: Robotic radical prostatectomy (RARP) is well established as a safe and effective treatment for prostate cancer. According to published studies, patients undergoing RARP are at increased risk of being diagnosed with an inguinal hernia after RARP and are four times more likely to have an inguinal hernia repair (IHR) following RARP. Several studies have demonstrated the effectiveness and safety of IHR during RARP. Overall, it has been observed that IHR adds on average, 12-15 min in total surgical time and there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Herniorrhaphy, onlay mesh totally extraperitoneal or transabdominal preperitoneal Celik, 27 S anchez-Ortiz, 13 Do, 28 Kyle, 29 Teber, 30 Rogers, 31 Nakamura 32 et al Herniorrhaphy mesh or mesh plug Joshi, 33…”
Section: Preoperativementioning
confidence: 99%
“…Herniorrhaphy, onlay mesh totally extraperitoneal or transabdominal preperitoneal Celik, 27 S anchez-Ortiz, 13 Do, 28 Kyle, 29 Teber, 30 Rogers, 31 Nakamura 32 et al Herniorrhaphy mesh or mesh plug Joshi, 33…”
Section: Preoperativementioning
confidence: 99%
“…2 Several studies have reported on RARP combined with R-TAPP, and a growing body of evidence supports the safety and feasibility of this combination. 3 Similarly, we report two cases in which RARP and R-TAPP were performed simultaneously. The unique aspect of this report is that in one case, extensive incision of the peritoneum during pelvic lymph node dissection made it impossible to close the peritoneal flap, but hernia repair was successfully completed by sewing an artificial polypropylene mesh over the hernia area in a circumferential fashion.…”
Section: Introductionmentioning
confidence: 75%
“…Moreover, Rogers et al . reported that although TAP hernioplasty during RARP increased surgical time, there was no increase in postoperative complications, suggesting that concomitant performance of both procedures is feasible and safe …”
Section: Preventive Measures From Open Surgery To Robotic Surgerymentioning
confidence: 99%
“…Moreover, Rogers et al reported that although TAP hernioplasty during RARP increased surgical time, there was no increase in postoperative complications, suggesting that concomitant performance of both procedures is feasible and safe. 23 Conversely, Ludwig et al compared concomitant laparoscopic TEP and RARP with similar combined IH repair with LRP. Following standard extraperitoneal RARP with pelvic lymph node dissection, surgeons performed TEP using the same ports.…”
Section: Ih Development After Rpmentioning
confidence: 99%